Purchase Decisions Reviewed From Lifestyle, Product Design, Brand Image of Iphone Smartphones Among Students of The Management Study Program at Batik Islamic University Of Surakarta - Rizal Malik; Ida Aryati; Ibnu Suryo (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to analyze the influence of lifestyle, product design, and brand image on iPhone smartphone purchase decisions among students of the Management Study Program at Universitas Islam Batik Surakarta. The phenomenon of iPhone usage among students is not only based on functional needs but is also influenced by lifestyle factors, product design, and brand image as symbols of social status and self-identity. This research employs a quantitative method with an explanatory research approach. The research population consists of 372 iPhone user students from the Management Study Program at Universitas Islam Batik Surakarta. A sample of 100 respondents was determined using purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis with SPSS version 26. The research findings indicate that: (1) Lifestyle has a positive and significant effect on iPhone purchase decisions (t-value = 7.037; sig. = 0.000); (2) Product design has a positive and significant effect on iPhone purchase decisions (t-value = 4.598; sig. = 0.000); (3) Brand image has a positive and significant effect on iPhone purchase decisions (t-value = 3.099; sig. = 0.003). Simultaneously, all three variables have a significant effect on purchase decisions (F-value = 56.040; sig. = 0.000). The Adjusted R Square value of 0.625 indicates that 62.5% of the variation in purchase decisions can be explained by lifestyle, product design, and brand image, while 37.5% is influenced by other factors outside the research model.